Association Between Environmental and Socioeconomic Risk Factors and Hepatocellular Carcinoma: A Meta-Analysis - Lu, Wenfeng; Zheng, Fengjiao; Li, Zhi; Zhou, Rui; Deng, Lugang; Xiao, Wenwei; Chen, Wenyan; Zhao, Rong; Chen, Yulan; Tan, Yuxing; Li, Zhibo; Liu, Limin; et al. (Frontiers in Public Health, 2022)
Background: The association between environmental and socioeconomic risk factors and the occurrence of hepatocellular carcinoma (HCC) is still inconclusive. A meta-analysis was conducted to address this issue. Methods: We systematically searched the databases including PubMed, Web of Science and Google Scholar and collected the related to risk factors of HCC before Mar. 6th, 2020. Statistical analysis was performed on the odds ratio (OR) value and 95% confidence interval (CI) of the correlation between environmental and socioeconomic factors and HCC. Begg rank correlation test, Eegg regression test and funnel plot were employed for identification of the publication bias. Results: 42 studies, a total of 57892 participants were included. Environmental and socioeconomic risk factors including ever educated (illiteracy), race (Black, Hispanic and Asian), medium- and low-incomes, occupations (farmer and labor), passive smoking, place of residence (rural), blood Aflatoxin B1 (AFB1) adduct level and exposure of pesticide, etc. were statistically increased with the HCC occurrence (P<0.05); and OR values and 95% CIs were 1.37 (1.00, 1.89), 2.42 (1.10-5.31), 1.90 (0.87-4.17), 5.36 (0.72-40.14), 1.48 (1.11,1.96), 1.74 (1.00-3.03), 1.49 (1.06-2.08), 1.52 (1.07-2.18), 1.43 (0.27, 7.51), 1.46 (1.09, 1.96), 2.58 (1.67-3.97) and 1.52 (0.95-2.42), respectively. We found 6-9, 9-12 and ≥12 years of education statistically reduced the risk of HCC occurrence (P<0.05); and OR values and 95% CIs were 0.70 (0.58, 0.86), 0.52 (0.40, 0.68), 0.37 (0.23, 0.59), respectively. No significant associations (P>0.05) were observed between race (Hispanic and Asian), passive smoking, marital status, place of birth, place of residence and HCC. In stratified analysis, exposure of pesticide was statistical significance (P<0.05) while race of black was on the contrary. Conclusions: Environmental and socioeconomic risk factors have greater impacts on the incidence rate of HCC. Improving national education and income levels can significantly reduce the HCC risk.